The Five-Factor Narcissism Inventory: A Five-Factor Measure of Narcissistic Personality Traits - Glover, Natalie; Miller, Joshua D.; Lynam, Donald R.; Crego, Cristina; Widiger, Thomas A. (Journal of personality assessment, 2012)
This study provides convergent, discriminant, and incremental validity data for a new measure of narcissistic personality traits created from the perspective of the Five-factor model (FFM) of general personality structure. Fifteen scales were constructed as maladaptive variants of respective facets of the FFM (e.g., Reactive Anger as a narcissistic variant of angry hostility), with item selection made on the basis of a criterion-keying approach using results from 167 undergraduates. On the basis of data from 166 additional undergraduates, the convergent validity of these 15 scales was tested with respect to 8 established measures of narcissism (including measures of both grandiose and vulnerable narcissism) and the respective facets of the FFM. Discriminant validity was tested with respect to facets from other FFM domains. Incremental validity was tested with respect to the ability of the FFM narcissism trait scales to account for variance in 2 alternative measures of narcissism, after variance accounted for by respective NEO PI-R facet scales and other established measures of narcissism were first removed. The findings support the validity of these new scales as measures of narcissistic personality traits and as maladaptive variants of the FFM.